Elementary Pre-service Teacher Education Programme in the Context of National Curriculum Framework–2005 A Study in Delhi - Jena, Prajnya Paramita (INDIAN EDUCATIONAL REVIEW, 2015)
The study focused on examining the status of elementary teacher education programme in Delhi in the context of National Curriculum Framework 2005. The objectives were to analyse the curriculum, to identify the infrastructure and learning activities of the teacher education institutions, to study the opinion of teacher educators, and to identify the problems (if any) faced by them in transacting the curriculum. Following the mixed methods approach, data were collected employing tools like categorisation matrix for content analysis, check list, and questionnaire. Results showed that the elementary pre-service education curriculum in Delhi has not been modified in accordance with NCF 2005. The availability of infrastructure in institutions was insufficient and learning activities were mechanical and formal as per syllabus. Various problems relating to transaction of curriculum were identified by the teacher educators.